(6a + b)2

Question

Asked 12/6/2010 8:49:04 AM

Updated 9/28/2014 7:39:35 PM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [9/26/2014 9:55:57 PM]

s

RinatisDinoro|Points 250|

twistedechoes|Points 26|

ambrosio_09|Points 725|

Expert answered|RinatisDinoro|Points 250|

Question

Asked 12/6/2010 8:49:04 AM

Updated 9/28/2014 7:39:35 PM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [9/26/2014 9:55:57 PM]

Rating

3

(6a + b)^2

= (6a+b)(6a+b)

= 36a^3 + 12ab + b^2

= (6a+b)(6a+b)

= 36a^3 + 12ab + b^2

Added 9/26/2014 11:25:16 PM

This answer has been flagged as incorrect.

Flagged by yeswey [9/28/2014 7:39:11 PM]

3

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2x + 32x - 112

= (2x + 32x) + (5 + - 112)

= 34 + - 107

= 5 + 2x + 32x - 112

= (2x + 32x) + (5 + - 112)

= 34 + - 107

Added 9/26/2014 11:26:25 PM

This answer has been flagged as incorrect.

Flagged by yeswey [9/28/2014 7:34:26 PM]

3

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

Added 9/28/2014 7:34:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/28/2014 11:11:47 PM]

3

(y^3 - 125) ÷ (y - 5)

=(y^3 - 5^3)/(y - 5)

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

=(y^3 - 5^3)/(y - 5)

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

Added 9/28/2014 7:37:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/28/2014 11:12:04 PM]

3

(6a + b)^2 = 36a^2 + 12ab + b^2

Added 9/28/2014 7:39:35 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/28/2014 11:11:50 PM]

0

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2{ x -4[3x + 14 - 7x)]}

= 5 + 2{ x -4[14 - 4x]}

= 5 + 2{ x - 56 + 56x }

= 5 + 2{ 57x - 56}

= 5 + 114x - 112

= 114x - 107

= 5 + 2{ x -4[3x + 14 - 7x)]}

= 5 + 2{ x -4[14 - 4x]}

= 5 + 2{ x - 56 + 56x }

= 5 + 2{ 57x - 56}

= 5 + 114x - 112

= 114x - 107

Added 9/26/2014 10:00:12 PM

This answer has been flagged as incorrect.

Flagged by jeifunk [9/26/2014 11:27:07 PM]

0

(y^3 - 125) ÷ (y - 5)

=( y^3 - 5^3) / (y -5)

= (y -5) (y^2 - 5y +5^2)/(y -5)

= y^2 -5y +25

=( y^3 - 5^3) / (y -5)

= (y -5) (y^2 - 5y +5^2)/(y -5)

= y^2 -5y +25

Added 9/26/2014 10:04:49 PM

This answer has been flagged as incorrect.

y9 ÷ y3 **Weegy:** = y3 **User:** -mnp(3m - 5n + 7p) **Weegy:** why don't you do homeworks? you think you will cheat all your life? (More)

Question

Expert Answered

Updated 3/9/2014 12:51:08 PM

2 Answers/Comments

y9 ÷ y3

= y^6

= y^6

Added 3/9/2014 12:50:03 PM

This answer has been confirmed as correct and helpful.

-mnp(3m - 5n + 7p)

= -3m^2np + 5mn^2p - 7mnp^2

= -3m^2np + 5mn^2p - 7mnp^2

Added 3/9/2014 12:51:08 PM

This answer has been confirmed as correct and helpful.

-mnp(3m - 5n + 7p) **Weegy:** why don't you do homeworks? you think you will cheat all your life? **User:** (6a + b)^2 **Weegy:** The equation is not complete. Can you provide me with the whole equation so that I can give you a solution? (More)

Question

Expert Answered

Updated 3/9/2014 12:52:40 PM

2 Answers/Comments

-mnp(3m - 5n + 7p)

= -3m^2np + 5mn^2p - 7mnp^2

= -3m^2np + 5mn^2p - 7mnp^2

Added 3/9/2014 12:51:47 PM

This answer has been confirmed as correct and helpful.

(6a + b)^2

(6a + b)(6a + b)

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

(6a + b)(6a + b)

36a^2 + 6ab + 6ab + b^2

= 36a^2 + 12ab + b^2

Added 3/9/2014 12:52:40 PM

This answer has been confirmed as correct and helpful.

48a3bc2 ÷ 3abc **Weegy:** 5 (More)

Question

Expert Answered

Updated 3/9/2014 12:47:00 PM

1 Answer/Comment

(48a^3bc^2) ÷ (3abc)

= 16a^2c

= 16a^2c

Added 3/9/2014 12:46:59 PM

This answer has been confirmed as correct and helpful.

(2p + 7)(3p - 9) **Weegy:** 6pp + 21p + 18 - 35 (More)

Question

Expert Answered

Updated 3/9/2014 12:48:15 PM

1 Answer/Comment

(2p + 7)(3p - 9)

6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

Added 3/9/2014 12:48:15 PM

This answer has been confirmed as correct and helpful.

31,268,191

questions answered

denyang

$216.05

Hearts 5,349 Views 1,542,869 Streams 622

phpmicro

$196.90

Hearts 4,134 Views 940,927 Streams 323

maydj

$194.15

Hearts 4,307 Views 1,132,020 Streams 428

sampi1890

$163.15

Hearts 4,608 Views 1,799,196 Streams 576

emdjay23

$152.05

Hearts 3,472 Views 854,106 Streams 275

miyaka

$150.25

Hearts 3,751 Views 946,481 Streams 492

Flora1988

$141.95

Hearts 3,586 Views 621,965 Streams 306

Peachygguk97

$139.05

Hearts 3,183 Views 402,054 Streams 206

There are no comments.